너비 4 .0 ㎜와 3 .2 ㎜공막낭을 이용한 연성인공수정체삽입술 후 절개창의 크기 변화 - 이동욱; Dong Wook Lee; 정영택; Young Taek Chung (Daihan angwa haghoi jabji, 1999)
소절개창 수술에서 각막절개도에 의해 형성된 절개창이 공막낭의 너비에 따라 수술 중 각막절개창의 확장 정도가 차이가 있는지 알아보기 위해 A군 2 5안에서는 너비 4 ㎜정도로 넓게 공막낭을 박리하였으며,B군 2 5안에서는 너비 3 .2 ㎜정도로 좁게 공막낭을 만든 후 수정체유화술과 연성인공수정체 삽입술을 실시하였다.수술중 특수하게 고안된 계측기를 이용하여 최초 각막절개창 형성 후 및 수정체유화술 후,연성인공수정체 삽입 후에 각막 절개창의 크기를 측정하였다.각막 절개창의 변화는 수정체유화술 후 A군과 B군 모두 평균 0 .0 5 ㎜,연성인공수정체 삽입 후 A군은 0 .1 5 ㎜,B군은 0 .0 5 ㎜의 절개창의 확장을 보였다. (p<0.01).창상의 안정도에는 두군 모두 차이가 없었으며,A군에서 -0.33D,B군에서 -0 .2 0 D의 유발난시가 술후 3개월에 있었다.그러므로 4 ㎜공막낭 수술은 3 .2 ㎜공막낭과 비교할 때 더 많은 각막 절개창 확장이 있고 유발난시가 컸으나 창상의 안정도는 차이가 없고 술자의 경우 기구 조작과 수정체 삽입이 용이하여 환자나 술자에 따라 적절한 공막낭의 너비를 선택할 필요가 있겠다(한안지 40:1529~1534,1999). Two different scleral tunnel incision widths were studied to determine whether the difference of cornea wound extension existed in each scleral tunnel incision widths (4 ㎜,3.2 ㎜).25 patients in group A undergoing phacoemu-lsification through approximately 4 ㎜width scleral tunnel and folded silicone IOL implantation were studied with internal incision gauge after initial keratome entry, phacoemulsification,and folded IOL implantation. Same procedure was done in group B patients except 3.2 ㎜scleral tunnel width was made instead.After completion of phacoemu- lsification,the incision was further widened by a mean of 0.05 ㎜in both groups.Forceps insertion of silicone IOL resulted in further incision enlargement by a mean of 0.15 ㎜in group A,and 0.05 ㎜in group B.No difference was found between the intraoperative or postoperative wound stabilities between two incisions.Vector analysis calculations of mean postoperative induced astigmatism for 4.0 ㎜incision versus 3.2 ㎜incision were -0.33D versus -0.20D at 3 month.Therefore,although 4 ㎜scleral tunnel incision resulted in larger wound extension and induced astigmatism,it showed same wound stability and easier implantation of IOL relative to 3.2 ㎜scleral tunnel incision.It is necessary that proper scleral tunnel incision width is selected based on degree of surgical skill and compliance of patients(J Korean Ophthalmol Soc 40:1529~1534,1999).